2022
DOI: 10.1136/bmjsem-2022-001319
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity on COVID-19-related symptoms and perception of physical performance, fatigue and exhaustion during stay-at-home orders

Abstract: ObjectivesThe measures used to contain the COVID-19 pandemic led to a significant reduction in physical activity. Due to the health benefits of exercise, recommendations were made for lockdown restrictions. Within the CoCo-Fakt study (Cologne-Corona counselling and support for index and contacts during the quarantine period), we aimed to determine how these recommendations were implemented, especially by individuals who were officially quarantined due to an infected persons (IPs) or as close contacts (CPs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…proved that positive emotions play a positive role in relieving negative emotions, improving resilience, and promoting emotional health. Relevant studies showed that physical activity plays an important role in promoting an individual's physical and mental health and creating positive emotions (Bouchard et al, 1994;Gehlhar et al, 2022). Based on the extended broaden-andbuild theory of positive emotions, this study attempts to discuss how physical activity affects emotional intelligence, resilience, and regulatory emotional self-efficacy.…”
Section: Literature Interviews and Hypotheses Developmentmentioning
confidence: 99%
“…proved that positive emotions play a positive role in relieving negative emotions, improving resilience, and promoting emotional health. Relevant studies showed that physical activity plays an important role in promoting an individual's physical and mental health and creating positive emotions (Bouchard et al, 1994;Gehlhar et al, 2022). Based on the extended broaden-andbuild theory of positive emotions, this study attempts to discuss how physical activity affects emotional intelligence, resilience, and regulatory emotional self-efficacy.…”
Section: Literature Interviews and Hypotheses Developmentmentioning
confidence: 99%
“… 233 , 237 239 Although physical activity decreased markedly during lockdown, physically active people were less likely, when infected, to report prolonged symptoms (OR 0.24; 95% CI 0.10, 0.55). 240 Similarly, closing schools led to severe adverse effects on children’s mental health and learning, yet were not effective at reducing the COVID-19 burden. 233 , 237 , 241 251 Not implementing lockdowns (including not closing schools), and explaining that they have a very negative cost–benefit ratio, is important.…”
Section: Implications For Management Of Long-covidmentioning
confidence: 99%
“…ist körperliche Aktivität kurz- und langfristig mit einem günstigeren physischen und psychischen Verlauf verbunden 6 . In einer eigenen Untersuchung konnten wir zeigen, dass sich aktive Menschen während einer gesetzlich verordneten Quarantäne als infizierte oder Kontaktperson weniger erschöpft und fitter fühlten 7 . Inaktive Personen wiesen hingegen ein höheres Risiko für einen schweren COVID-10 Verlauf auf 8 .…”
Section: Introductionunclassified